Financial Management Innovation through Digipay at the Lamandau Regency Ministry of Religious Affairs Office - Farid Zaky Yopiannor; Munawarah Munawarah (Syntax Idea)
The boom in online transactions has also become a momentum for MSMEs to be able to go public or become better known to the public. By entering the marketplace, MSMEs have the opportunity to move up in class because they have shifted from initially only carrying out conventional (cash) transactions to digital (cashless). Digipay is a digital payment application system using Government Credit Cards (KKP) and/or CMS Virtual Accounts developed by the Ministry of Finance in collaboration with Himbara Bank. The ecosystem is formed from the APBN Money Supply (UP) Management Working Unit and vendors/shops/stalls/etc. (MSMEs) based on accounts at the same bank. Digital Payment - Marketplace integrates APBN user spending units, MSMEs as providers of goods/services, and banking in one ecosystem. This research aims to find out how Digipay Management Innovation is at the Lamandau Regency Ministry of Religion Office? And What are the supporting and inhibiting factors for implementing digipay at the Lamandau Regency Ministry of Religion Office. This research is descriptive research using a qualitative approach to library research and field research and in an effort to obtain real data using observation techniques and interview techniques. The research results show that financial management through Digipay at the Ministry of Religion, Kab. Lamandau in 2023 is not yet optimal and still needs to be further improved. The inhibiting factors include the mindset of the work unit and business actors, limited human resources for financial managers/lack of user capacity on the part of the financial management work unit which only focuses on a handful of employees. To further optimize and expand the use of the Digipay application, there are three things that need to be done. Firstly, regulations for imposing sanctions on work units that do not use Digipay are established. Second, more massive socialization, to business actors (MSMEs) and cooperatives so that they are more familiar with the Digipay application and become involved as vendors in procuring government goods and services. The three additional employees who have the capacity to manage finances at the Ministry of Religion of Lamandau Regency